2019
DOI: 10.3390/ijms20205084
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α Suppresses the Activation of TGF-β/Smad Signaling via Targeting TGFβRI Downregulation by let-7b/c Upregulation

Abstract: TGF-β/Smad signaling is a major pathway in progressive fibrotic processes, and further studies on the molecular mechanisms of TGF-β/Smad signaling are still needed for their therapeutic targeting. Recently, peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α) was shown to improve renal fibrosis, making it an attractive target for chronic kidney diseases (CKDs). Here, we show the mechanism by which PGC-1α regulates the TGF-β/Smad signaling pathway using HK-2 cell lines stably overexpressing empt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…TGFβ1 is a major inducer of EMT through transcriptional reprogramming with SNAI1, SNAI2, ZEB1, and ZEB2 as well as TWIST1 [ 7 ]. Recent report has shown that PGC1α suppresses TGFβ1/Smad signaling through let-7b/c upregulation [ 52 ]. In addition, suppression of ID1 and ID2 expression by TGFβ1/Smad signaling has been previously observed [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ1 is a major inducer of EMT through transcriptional reprogramming with SNAI1, SNAI2, ZEB1, and ZEB2 as well as TWIST1 [ 7 ]. Recent report has shown that PGC1α suppresses TGFβ1/Smad signaling through let-7b/c upregulation [ 52 ]. In addition, suppression of ID1 and ID2 expression by TGFβ1/Smad signaling has been previously observed [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is triggered by many signaling molecules, which interplay with each other to form a crosstalk network. TGF-b signaling, which acts via Smad proteins with intrinsic receptor tyrosine kinase activity, is one of the most important pathways of EMT (Choi et al, 2019). In addition, bone morphogenetic protein, Notch, and Hedgehog activated by various dynamic stimuli from the local microenvironment are also motivators of EMT (Gonzalez and Medici, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that let-7b is negatively correlated with collagen I and TGFβI [ 24 , 25 , 26 , 27 ], leading us to wonder whether collagen I and TGFβI were target genes of let-7b. We transfected either a let-7b mimic or inhibitor into LX-2 cells.…”
Section: Resultsmentioning
confidence: 99%